Colorants in foods – from past to present - Harasym, Joanna; Bogacz-Radomska, Ludmiła (Engineering Sciences And Technologies, 2016)
Consumer expectations toward food products are changing due to the development of the food industry and new technologies. The growing knowledge in the field of health impact of natural and artificial colorants added to food results in an awaking interest of natural dyes among researchers, producers and consumers. Food colour plays a fundamental role in identifying the quality of food, so it is associated with the sensory quality of food products. In this paper the different types of colorants, their production methods and the evolution of these methods were characterized
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 3 (22), s. 21-35
Keywords: colorants; food colouring; natural pigments; synthetic dyes; barwniki; barwniki spożywcze; naturalne pigmenty; barwniki syntetyczne